Voçoroca que nos move a refletir e agir - Souza, Aracelly Oliveira Franco; Barros, Cleber Mirando; Oliveira, Eddiney Nunes; Novais, Maria Cleide Farias; Nunes, Geisa Oliveira; Araújo, Inês Cassia Lima Silva; Afonso, Jakelaine Gregorio; Alves, Joana Darc Xavier; Souza, Vanderleia Costa; Maia, Vanilda Fatima (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf